An Analysis of Strategic Importance of Executive Education: Its connection to Organizational Success - Munyao, Joseph Mbutu; Musuu, Gladies Koki (European Journal of Business and Strategic Management, 2025)
Purpose: This article analyses the strategic importance of executive education towards the success of organizations. Methodology: This study used a qualitative research design and looked at correlational aspects of different variables. This provided an in-depth understanding of the variables, experiences, drivers, and behaviours. The data collected was analyzed via an explanatory discussion. A secondary type of data collection was applied from sources such as books, published journal articles, online publications etc. Findings: The study found that there was a positive connection between the Executive Education and employee performance, which trickles down to organizational performance. It was concluded that there was a significant Strategic Importance of Executive Education to Organizational Success. Unique Contribution to Theory, Practice and Policy: The study was based on two major theories, i.e. Human Capital Theory (HCT), Becker, G. S. (1993), and Equity Theory (ET), Adams, J. S., & Freedman, S. (1976). Based on these two theories, the study explored the interaction between executive education, training and Development, employee empowerment, strategic leadership and continuous organizational learning culture and the connection therein with organizational success.